Physicochemical Characterization and Epoxidation of Jatropha Curcas Oil for Eco-Friendly Engine Lubricant Applications - Putra, Agus Dwi; pradani, Yayi Febdia; Dewi Izzatus Tsamroh; Zakaria, Yahya; Mahfudi Sahli Subandi (Universitas Negeri Gorontalo, 2025)
This study aims to explore the potential of castor oil (Jatropha curcas L.) as a plant-based alternative engine lubricant and compare it to commercial mineral-based lubricants. The research process includes drying Jatropha seeds and epoxidizing the oil using oxidizing agents (H₂O₂) and (CH₃COOH) with variations of (1:0.075; 1:0.15; 1:0.225; and 1:0.30). Chemical testing was conducted to analyze the acid number of the oil, while physical testing was carried out to measure its viscosity index, flash point, and pour point. The results show that Jatropha oil has an acid number of 5.30, a viscosity index of 217, a flash point of 270°C, and a pour point of 0°C. Therefore, Jatropha oil demonstrates potential as a base material for engine lubricants due to its relatively high flash point, which approaches that of polyol ester (POE)-based oils. However, further modification with additives is required to lower its pour point, ensuring it remains fluid in colder climates such as those in subtropical regions.